ï¨-Duals of Some Double Sequence Spaces - Gupta, K B; Ansari, Ashfaque A (Journal of Experimental Sciences, 2012)
P. Chandra and B.C. Tripathy [13] have generalized the notion of the köthe-toeplitz dual of sequence spaces on introducting the concept of h-dual of order r, for r ³ 1 of sequence spaces. B.C. Tripathy and B. Sharma [3] have introduced the notion of ï¨-dual of order r, for r ³1 of double sequence spaces. Ansari and Gupta [1] have generalized the notion of the köthe-Toeplitz dual of sequence spaces on introducing the concept of h-dual of order r, for 0 < r £ 1 of sequence spaces. In this paper, we have defined and determined the ï¨-dual of some double sequence spaces for 0 < r £ 1 and have establised their perfectness in relation to ï¨-dual for 0 < r £ 1.